Disabled upon arrival eugenics, immigration, and the construction of race and disability - Dolmage, Jay (The Ohio State University Press, 2018)
"A rhetorical examination of the spaces, technologies, and discourses of immigration restriction during the peak period of North American immigration in the early twentieth century. Links anti-immigration rhetoric to eugenics...and argues racist and ableist ideas about bodily values have never really gone away"...
Includes bibliographical references and index
Keywords: Geschichte 1900-1930; Eugenics -- Social aspects -- United States; Eugenics -- Social aspects -- Canada; Rhetoric -- Social aspects -- United States; Rhetoric -- Social aspects -- Canada; People with disabilities -- Social aspects; Eugenik; Behinderter Mensch; Einwanderung; United States -- Emigration and immigration -- Social aspects; Canada -- Emigration and immigration -- Social aspects; USA; Kanada